Making Bishops in Tridentine France: The Episcopal Ideal of Jean-Pierre Camus - Forrestal, Alison (The journal of ecclesiastical history, 2003)
The experience of Jean-Pierre Camus, a reforming bishop in seventeenth-century France, highlights the problematic ambivalences present within French Catholic reform after the Council of Trent: the persistent tensions between bishops, the papacy and lower clergy over the most effective means of achieving renewal and the most appropriate forms of ecclesiastical government, as well as the growing emphasis upon episcopal perfection within an episcopate that was, paradoxically, closely linked to politics and secular society. His publications on episcopacy provide an insight into the motivations and beliefs of a prominent episcopal reformer and into the ecclesiastical culture of seventeenth-century France. This article seeks to demonstrate that Camus' episcopal ideal was a coherent adaptation of traditional and contemporary views produced in response to post-Trent circumstances and that the bishop's published views had a significant impact upon his fellow prelates and their relationship with the papacy.